Obtaining materials from sargassum for use in an energy storage device - Adriana Cervantes-Mendiola; Ulises León-Silva; María Elena Nicho; J. Jesús Escobedo-Alatorre; Jorge Arturo Sandoval-Espino; Alfredo Olarte-Paredes; René Salgado-Delgado (Revista Facultad de Ingeniería Universidad de Antioquia, 2025)
Sargassum has become an “ecological disaster” on most beaches in the Caribbean Sea, causing serious health, safety, economic and environmental problems. The objective of this study was to valorize sargassum for the extraction of sodium alginate, cellulose and cellulose nanocrystals. Cellulose was also used in the manufacture of a separator for an energy storage device (ESD) based on expanded graphite and activated carbon. Sargassum was characterized physicochemically; the results of this characterization are very relevant for the generation of bioenergy and removal of toxic contaminants. The extracted materials were identified by FT-IR; the spectra were very similar to the IR spectra of commercial samples, which corroborated that the materials extracted were sodium alginate, cellulose and cellulose nanocrystals. The performance of the ESD/cellulose-based separator was determined using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Additionally, an RC circuit and an oscilloscope were used to perform a charge/discharge test. The voltammograms obtained for the ESD showed a rectangular shape with redox peaks characteristic of a pseudocapacitor and a battery, and the Nyquist plot showed a typical electrochemical performance of such ESD. Likewise, the developed devices have the capacity to store and release energy in seconds.